2023
DOI: 10.1002/alz.13407
|View full text |Cite
|
Sign up to set email alerts
|

The heritability of blood‐based biomarkers related to risk of Alzheimer's disease in a population‐based sample of early old‐age men

Nathan A. Gillespie,
Jeremy A. Elman,
Ruth E. McKenzie
et al.

Abstract: INTRODUCTIONDespite their increased application, the heritability of Alzheimer's disease (AD)–related blood‐based biomarkers remains unexplored.METHODSPlasma amyloid beta 40 (Aβ40), Aβ42, the Aβ42/40 ratio, total tau (t‐tau), and neurofilament light (NfL) data came from 1035 men 60 to 73 years of age (μ = 67.0, SD = 2.6). Twin models were used to calculate heritability and the genetic and environmental correlations between them.RESULTSAdditive genetics explained 44% to 52% of Aβ42, Aβ40, t‐tau, and NfL. The Aβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…To our knowledge, only one twin study – not including p-tau217 – has investigated the heritability of blood-based AD biomarkers. 4 We found that age and APOE genotype, but not ADPRS (based on cases having clinical diagnosis of AD), were significant predictors of continuous p-tau217 levels but also AD pathology as indicated by abnormal levels of plasma p-tau217 using published cut-offs for amyloid and tau positivity. 1 For the ADPRS, we chose to use the score based on Lambert et al (2013).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…To our knowledge, only one twin study – not including p-tau217 – has investigated the heritability of blood-based AD biomarkers. 4 We found that age and APOE genotype, but not ADPRS (based on cases having clinical diagnosis of AD), were significant predictors of continuous p-tau217 levels but also AD pathology as indicated by abnormal levels of plasma p-tau217 using published cut-offs for amyloid and tau positivity. 1 For the ADPRS, we chose to use the score based on Lambert et al (2013).…”
Section: Discussionmentioning
confidence: 71%
“…Only one twin study has investigated the heritability of AD plasma biomarkers and found that about half of the variance in beta-amyloid (Aβ)42 and Aβ40 was explained by additive genetic effects whereas Aβ42/40 had zero heritability; also plasma total tau had 50% heritability. 4 However, twin studies have not investigated the heritability of plasma p-tau217 despite its promise as an accurate cost-effective biomarker of both amyloid and tau positivity. 1 The large case-control genome-wide association studies (GWAS) of AD have indicated over 80 loci.…”
mentioning
confidence: 99%